Humor como forma de cuidar: a transdisciplinaridade e as possibilidades de trans-formação na educação em saúde - Marques, Marcelo dos Santos (2015)
This study takes a look at the transformative potential of transdisciplinary education, in contrast to the reductionist thinking of the current establishment, showing how reductionism is still strong in higher education institutions, despite the findings of quantum physics, dated at the beginning of the last century. The research subjects are students of undergraduate and graduate of the Faculty of Medicine, Federal University of Goiás (UFG). The transdisciplinary model of education was inserted into the medical school UFG through two elective courses: the first is Pronto Sorriso, this is a free core for the graduate students of the Faculty of Medicine and other areas of health; the second discipline is the Humor in Care, offered in the graduate programs in Health Sciences and Health Education. The use of humor as a tool to break the rigidity of the health professional attitude towards the patient, opens the possibility of care holistic treatment instead of fragmented, serving as a counterpoint to the biomedical model that brought aridity to sterile hospital landscape and the relationship patient caregiver. The problem raised in this research was to investigate how the paradigm shift and the inclusion of education transdisciplinary model are contributing to the humanization, the cross-training of students and changing landscape in health education. The theoretical showed the hype caused by the biomedical model robotized work of health professionals by placing them on a pedestal that only causes distancing from the patient. Therefore, the objective was to analyze and evaluate the relevance of transdisciplinary education in crosstraining of the above students, focusing on the teaching-learning relationships and patient caregiver and perception of the landscape where they are inserted. The justification of this research is in urgent transformation of the biomedical model. The increasingly verticalized and further development of medical science is reducing the service, almost exclusively, to the pathology. The health worker is getting insensitive and teaching model in medical colleges are getting sick students. For the survey data I utilized as instrument the Clowns doctors’ reported visits produced by the graduate students, the texts assessment completion of Humor discipline in Caring for graduate students, interviews with monitors from Pronto Sorriso and notes made over the years teaching at UFG. The analysis was performed according to the parameters of Laurence Bardin content analysis, separating the data into categories for later interpretation. As a result we can say that the Pronto Sorriso and Humor in Care are trans-forming educational practices that contribute to the rescue of humanization of health professionals. There is a great satisfaction and gratitude of the students because they belong to a project that was meaningful to the people they watched, demonstrating clearly that treating only the conditions is no longer enough, revealing the search for a new position in caregiver - patient relationship . The project developed within the UFG is presented as effective model of transdisciplinary education that contributes to a new vision in the training process of health professionals, may serve as an example to other higher education institutions. Finally, I present the systematization of the games and discussions that have been developed over the years of work teaching at UFG, are possibilities to assist other educators who perchance resolve go down that route. Currently, the model reported in this research has reached the Faculty of Medicine, PUC-Goiás, School of Medicine UniEVANGÉLICA in Annapolis, the Faculty of Medicine of Araguaína in Tocantins and the Faculty of Education of the State University of Mato Grosso. Finally it is concluded that transdisciplinarity is transforming agent of the landscape and the status quo, thus a transformative opportunity for the model of science and hegemonic education in health education.